Absorption-based post-combustion capture of carbon dioxide - Feron, Paul H. M. (Duxford, UK : Woodhead Publishing is an impring of Elsevier, 2016)
Absorption-Based Post-Combustion Capture of Carbon Dioxide provides a comprehensive and authoritative review of the use of absorbents for post-combustion capture of carbon dioxide. As fossil fuel-based power generation technologies are likely to remain key in the future, at least in the short- and medium-term, carbon capture and storage will be a critical greenhouse gas reduction technique. Post-combustion capture involves the removal of carbon dioxide from flue gases after fuel combustion, meaning that carbon dioxide can then be compressed and cooled to form a safely transportable liquid that can be stored underground. Provides researchers in academia and industry with an authoritative overview of the amine-based methods for carbon dioxide capture from flue gases and related processes Editors and contributors are well known experts in the field Presents the first book on this specific topic.
Includes index.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Carbon sequestration; Carbon dioxide -- Absorption and adsorption; TECHNOLOGY & ENGINEERING -- Environmental -- General; Carbon dioxide -- Absorption and adsorption; Carbon sequestration; Electronic books